Buccal mucosa versus skin graft for two-stage redo hypospadias repair: our centre experience - Yekolla, Yuvaraju; Muppirala, Lakshmi Ramesh; Pogula, Vedamurthy Reddy; Gaddam, Yaswanth Kumar; Bathalapalli, Ravi Theja; Gupta, Atul (International Journal of Research in Medical Sciences, 2025)
Background: Repeated surgical interventions for significant problems arising from either partial or complete failure of hypospadias treatment are less likely to succeed due to extensive scarring, considerable shortening of the penis, and scarred, hypovascular skin over the penile area. We provide the outcomes of our surgical experience with staged reoperation utilizing buccal mucosa and skin grafts in the correction of hypospadias in patients with problems following multiple failed surgeries. Methods: The study was carried out in the department of urology, Narayana Medical College and Hospital, Nellore between January 2023 to March 2025. Depending on the type of free graft used for urethroplasty, patients are divided into two groups. Group A-treated with buccal mucosa graft. Group B-treated with skin graft. Data were analyzed using SPSS version 26.0 statistical software. Results: The results showed that regarding early complications, patients in the BMG group showed a numerically lower incidence of graft loss (0% vs. 20%), fistula (0% vs. 10%), infection (9.09% vs. 20%), and meatal stenosis (9.09% vs. 20%) compared to the skin graft group; however, these differences were not statistically significant (p>0.05). At the same time, there were no reported cases of graft contracture and urethral stricture. The incidence of donor site morbidity was greater in the skin graft cohort than in the BMG cohort. Conclusions: Our findings indicated that BMG urethroplasty was associated with reduced occurrence of postoperative problems and donor site morbidity compared to skin graft urethroplasty. Furthermore, research is necessary to validate our findings and determine the subgroup of patients who are appropriate candidates for BMG urethroplasty.